INTEREST SCALES FOR VOCATIONAL HIGH SCHOOL STUDENT OF SMKN 3 BENGKULU CITY - Hidajat, Selvia Tristianty (UNIB Press, 2016)
Abstract: This research is aimed to result the interest scale which is used as directive of the student at the program of competence at SMKN 3 Kota Bengkulu. The interest scale is aimed to see the suitability of choice with the students interest at one of the competence program food science, clothing science, beauty clas, computer net technique, and broadcasting. The counseling teacher is hoped to be able to identify and make the recomendation of students interest purpose. The implementation of the interest scale shows that there are students who have not suitable placed the class at skill program they have already chosen. The data analysis result individual profil, group profil, graph and recomendation. The researcher further more can develope other non tests instrument to facilitate the students placement.Vocational Educato